2023
DOI: 10.3389/fimmu.2023.1142088
|View full text |Cite|
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cell-derived exosomes promote murine skin wound healing by neutrophil and macrophage modulations revealed by single-cell RNA sequencing

Abstract: IntroductionFull-thickness skin wound healing remains a serious undertaking for patients. While stem cell-derived exosomes have been proposed as a potential therapeutic approach, the underlying mechanism of action has yet to be fully elucidated. The current study aimed to investigate the impact of exosomes derived from human umbilical cord mesenchymal stem cells (hucMSC-Exosomes) on the single-cell transcriptome of neutrophils and macrophages in the context of wound healing.MethodsUtilizing single-cell RNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
0
9
1
Order By: Relevance
“…Perhaps Clec4e expression in macrophages and neutrophils can be used as an indicator to identify the different factors contributing to ARDS. Retnlg has been shown to be associated with neutrophil migration ( 39 , 40 ), whereas in our study, Retnlg present in top50 DEGs of multiple cell clusters in the pulmonary ALI, was not found in the DEGs of neutrophils. S100 Calcium Binding Protein A9 (S100a9) usually present as a heterodimer in vivo , mainly released by immune cells, such as neutrophils and macrophages ( 41 ), and is an early-warning protein for inflammation, initiated by Toll-like Receptor 4 (TLR4) in response to LPS stimulation ( 42 ).…”
Section: Discussioncontrasting
confidence: 84%
“…Perhaps Clec4e expression in macrophages and neutrophils can be used as an indicator to identify the different factors contributing to ARDS. Retnlg has been shown to be associated with neutrophil migration ( 39 , 40 ), whereas in our study, Retnlg present in top50 DEGs of multiple cell clusters in the pulmonary ALI, was not found in the DEGs of neutrophils. S100 Calcium Binding Protein A9 (S100a9) usually present as a heterodimer in vivo , mainly released by immune cells, such as neutrophils and macrophages ( 41 ), and is an early-warning protein for inflammation, initiated by Toll-like Receptor 4 (TLR4) in response to LPS stimulation ( 42 ).…”
Section: Discussioncontrasting
confidence: 84%
“…Previously, we characterized the heterogeneity of neutrophils and macrophages during HucMSC-Exo-mediated tissue repair through single-cell sequencing. 16 Herein, we found that the pro-healing effect of HucMSC-Exo heavily depended on infiltrated neutrophils rather than macrophages. Adding complexity to this, HucMSC-Exo guided the phenotypic switching of neutrophils at the wound site, directly reprogramming naïve neutrophils (N0) into an anti-inflammatory proangiogenetic status (N2).…”
Section: Introductionmentioning
confidence: 75%
“…Our prior recognition of the participation of myeloid cells, specifically macrophages and neutrophils, in the wound healing process led us to investigate their role in HucMSC-Exo-guided wound healing. 16 We deployed two strategies to selectively deplete either circulating monocytes (via anti-F4/80 treatment) or neutrophils (via anti-Ly6G) in recipient mice ( Figure 2A ). Intraperitoneal injection of the anti-Ly6G antibody resulted in the effective depletion of neutrophils without affecting circulating monocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are accompanied by shifts in ligand-receptor interactions, ultimately promoting a conducive environment for healing. 52 HucMSC-EXOs have significant effects on the regulation of microglia activation in dorsal root ganglia (DRGs) 53 and suppress macrophages in peripheral nerves. 54 Exosomes from alternative stem cell sources, such as bone marrow mesenchymal stem cells, 55 gingival mesenchymal stem cells, 56 and Schwann cells, 57 among others, affect dorsal root ganglion (DRG) neurons, and promote peripheral nerves regeneration.…”
Section: Discussionmentioning
confidence: 99%